GOLDILOCKS AND THE BEAR: TRANSFORMATION OF FAIRY TALES AND POLITICAL CODES - Rasiah, Rasiah; Gratiwi, Novia; Muarifuddin, Muarifuddin (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
Goldilocks and The Bear is a novel transformed from The Story of the Three Bears and Aladdin and Magic Lamp fairy tales. The novel presents a non-linear plot since it mixed up the plot and characters from those fairy tales as its hypo-grams. The process of the mixture is surely not merely innovation, but it has a politic code appeared in it. This study is investigating the transformation the fairy tales into the novel, and entails the political code behind it. Hutcheon’s concept of poetics and politics of postmodernism is used to display the novel through its double sides; its structure (as well as its contexts) and ideological sphere. This study suggests that the novel is using and distorting in the fairy tales through the women characters; Goldilocks named Victoria, a new women character Safiyya, Bear male as Ramsey as representation of white male, and Aladdin as dark-skinned man. The composition of the characters actually represented political codes of gender and white supremacy in Western narrative. It is legitimating and subverting the narrative representation of woman and dark skinned people who used to be placed as marginal people in the western narrative. The novel, reversaly, raised other possibility that those peripheral characters (women and blacks) can be competed with central character (men and whites). The narrative text of Goldilocks and the Bear displayed the deconstruction of women and black characters who used to be depicted in negative label in literature and cultural product, especially in Western representation.